PENGARUH PENAMBAHAN HIGH FRUCTOSE SYRUP (HFS-55) TERHADAP KARAKTERISTIK RED WINE KELOPAK BUNGA ROSELA (Hibiscus sabdariffa L.) - Pratiwi, Anastasia Laksmi; Duniaji, Agus Selamet; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPA, 2019)
This research was aimed to determine the effect of adding high fructose syrup (HFS-55) to red wine made from roselle flower petals that can produce roselle red wine with the best characteristics. This study used a Completely Randomized Design (RAL) with a treatment of adding HFS-55 10%, 15%, 20%, 25%, 30%. This treatment was repeated 3 times, resulting in 15 experimental units. The data were analyzed by ANOVA and followed by Duncan test. The results showed that the adding of HFS-55 on roselle red wine has a significant effect on ethanol content, pH, total soluble solid, total reducing sugar, aroma, taste and overall acceptance with the best treatment was obtained from the addition of 25% HFS-55 with roselle red wine characteristics containing 10.65% ethanol content, pH 3.6, total soluble solids 10.10% Brix, total reducing sugar 10.37%, total phenolic 3.08 mg/ml and total methanol was not found, and with the panelist preference for color usual, aroma rather like, taste rather like and overall acceptance rather like. Keyword : roselle, HFS-55, red wine